Pengaruh Latihan Fisik dan Keterampilan Motorik terhadap Performa Atlet Badminton Pemula - Novita Sari; Halia Octavia; Maelan Dwi Br Banurea; Vany Nove Try Aidiva (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze the effect of physical training and motor skills on the performance of novice Badminton athletes. The method used in this research is quantitative method using associative approach. Quantitative research is a research method based on the philosophy of positivism, which is used to examine certain populations or samples with 35 respondents. The results showed that Physical Training (X1) on Badminton Athlete Performance These results show that the t value for the variable (X1) Physical Training is greater than the t table, namely 2.082> 1.69236, and the Sig value for the variable (X1) Physical Training is less than 0.05, namely 0.002 <0.05. Motor Skills shows that the t value for the variable (X2) Motor Skills is greater than the t table, which is 3.455 > 1.69236, and the Sig value for the variable (X2) Motor Skills is also less than 0.05, which is 0.000 < 0.05. Therefore, it can be concluded that Ha2 is accepted and Ho2 is rejected. Physical Training (X1) and Motor Skills (X2) on the Performance of Badminton Y Athletes simultaneously show the results of the F test showing that the calculated F value is greater than the F table, which is 30.700> 3.29, and the Sig value is also less than 0.05, which is 0.000 < 0.05. Thus, it can be concluded that in the F test, Ha3 is accepted and Ho3 is rejected. This means that simultaneously, Physical Training (X1) and Motor Skills (X2) have a significant influence on the Performance of Badminton Athletes as variable Y.